Modified Hungarian Method for Solving Balanced Fuzzy Transportation Problems - Fried Markus Allung Blegur; Nugraha K. F. Dethan (Jurnal Varian, 2022)
This paper discusses how to solve balanced transportation problems, with transportation costs in the form of trapezoidal fuzzy numbers. Fuzzy costs are transformed into crisp costs using the Robust’s method as a ranking function. A new approach of modified Hungarian method has been applied to solve the problem of fuzzy transportation. This approach solves the fuzzy transportation problem in one stage of optimization and yields the same results as other methods that solve the problem in two stages.